Prevalence and Associated Risk Factors of Urinary Schistosomiasis among Primary School Pupils in the Jidawa and Zobiya Communities of Jigawa State, Nigeria - J. B. Balogun; B. Adewale; S. U. Balogun; A. Lawan; I. S. Haladu; M. M. Dogara; A. U. Aminu; C. R. Caffrey; H. P. De Koning; Y. Watanabe; E. O. Balogun (Annals of Global Health, 2022)
Background: Urogenital schistosomiasis (UgS) is a parasitic disease caused by 'Schistosoma haematobium' and can lead to chronic ill-health. Nigeria is endemic for schistosomiasis, but epidemiology of UgS has not been studied in most states. This study was conceived with the aim to contribute towards an accurate national picture of UgS in Nigeria. The prevalence of UgS and the associated risk factors were for the first time investigated among primary school pupils in Jidawa and Zobiya communities of the Dutse Local Government Area (LGAs) of Jigawa State, Nigeria. Method: Focus group discussions with teachers and parents were conducted. After obtaining written consent from parents, questionnaires were administered to pupils to obtain socio-demographic data and information on water contact activities. Urine samples (279) were collected and processed by the urine filtration technique to evaluate haematuria and the presence of 'S. haematobium' eggs. Results: Prevalences of 65.7% (90/137) and 69.0% (98/142) were recorded in the Jidawa and Zobiya communities, respectively. In both communities, there was a significant association between gender and UgS: 63.3% of the infected pupils were males as compared to 36.7% females (χ2 = 5.42, p = 0.020). Grade 5 students had a significantly higher prevalence (χ2 = 17.919, p = 0.001) (80.0%) compared to those in grades 2, 3, 4, and 6 (63.8%, 66.7%, 61.5%, and 64.6%, respectively). Water contact activities showed that pupils involved in fishing, irrigation, and swimming were at greater risk of becoming infected in Jidawa and Zobiya, with odds ratios (risk factors) of 5.4 (0.994–28.862) and 4.1 (1.709–9.862), respectively (p = 0.05). Conclusion: Both the Jidawa and Zobiya communities of the Dutse LGAs of Jigawa State are hyperendemic for UgS. In collaboration with the State Ministry of Health, mass administration of praziquantel was carried out in the Jidawa and Zobiya communities after this study.